Sterilisasi Paksa Oleh Pemerintah Tiongkok Terhadap Perempuan Etnis Uighur: Perspektif Hukum Hak Asasi Manusia Internasional - Salsabila, Evelyn; Pradnya Dewi, Tjokorda Istri Diah Widyantari (Kertha Wicara : Journal Ilmu Hukum; Vol 10 No 1 (2020), 2020)
This study aims to acknowledge the perspective of international human rights law regarding the involuntary sterilization policy implemented by the Government of China against Uighurs women. The research method used is juridical-normative research methodology using statutory and conceptual approach which focus on studying various international legal instruments and other legal materials relating to China's implementation of forced sterilization against Uighurs women and human rights protection for them. Based on the study, writer acknowledges that the involuntary sterilization policy implemented by the Government of China is violating the human rights of Uighurs women as regulated in numerous applicable human rights legal instruments.   Key Words: Involuntary Sterilization, Human Rights, Uighurs Women